2019
DOI: 10.2105/ajph.2019.305193
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Utilization Before and After a Natural Disaster in the 2016 Baton Rouge–Area Flood

Abstract: Objectives. To understand changes in behavioral health services utilization and expenditures before and after natural disaster with an adult Medicaid population affected by the Baton Rouge, Louisiana–area flood (August 2016). Methods. We examined de-identified behavioral health claims data for Medicaid-insured adults in the affected region for 10 months before and after flooding (October 2015–June 2017). This constituted 273 233 provider claims for 22 196 individuals. Claims data included patient gender, beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 15 publications
0
16
0
2
Order By: Relevance
“…Home flooding is a serious public health problem that has long lasting health impacts for people who experience it [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Microbial toxins such as molds and fungus are known to worsen respiratory problems and are associated with the development of asthma and allergic rhinitis [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Home flooding is a serious public health problem that has long lasting health impacts for people who experience it [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Microbial toxins such as molds and fungus are known to worsen respiratory problems and are associated with the development of asthma and allergic rhinitis [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Disaster medicine studies have demonstrated that mental health impacts of a disaster event can be noted at the population level nearly a year after resolution. 63 Within the context of violent trauma in particular, hospital registries have shown increased incidence and increased acuity for at least six months following a discrete event. 64 In contrast, the COVID-19 pandemic is on-going, with various national, regional, and local lockdowns going in and out of effect according to the status of infections in each locale.…”
Section: Methods Of Studymentioning
confidence: 99%
“…Flooding and extreme precipitation present serious risks to mental and physical health [13][14][15][16][17][18][19][20][21][22]. Mental impacts from flooding and extreme precipitation include psychological distress and trauma [23][24][25].…”
Section: Introductionmentioning
confidence: 99%